Calcium Pyrophosphate Dihydrate Crystal Deposition in Gouty Tophi. Issue 2 (5th December 2020) - Ea, Hang‐Korng; Gauffenic, Alan; Nguyen, Quang Dinh; Pham, Nhu G.; Olivier, Océane; Frochot, Vincent; Bazin, Dominique; Le, Nghia H.; Marty, Caroline; Ostertag, Agnès; Cohen‐Solal, Martine; Laredo, Jean‐Denis; et al.
Abstract : Objective: The coexistence of calcium pyrophosphate dihydrate (CPPD) and monosodium urate monohydrate crystals in gouty tophi has rarely been reported. We undertook this study to investigate CPPD crystal deposits in a series of surgically removed gouty tophi and to identify factors associated with these deposits. Methods: Twenty‐five tophi from 22 gout patients were analyzed using polarized light microscopy, field emission scanning electron microscopy (FESEM), and μ Fourier transform infrared (μFTIR) spectroscopy. Results: Tophi consisted of multiple lobules separated by fibrous septa and surrounded by a foreign‐body giant cell reaction. CPPD crystal aggregates were identified in 9 of 25 tophi from 6 patients. CPPD crystals were dispersed or highly compacted, localized at the edge or inside the tophus lobules, with some lobules completely filled with crystals. Both monoclinic and triclinic CPPD crystal phases were identified using FESEM and μFTIR. Compared to patients without CPPD, those with CPPD‐containing tophi were older (mean 60.5 years versus 47.2 years; P = 0.009), and had longer‐term gout duration (mean 17.0 years versus mean 9.0 years; P < 0.05) and tophi duration (mean 10.0 years versus mean 4.6 years; P < 0.01). None of the patients had radiographic chondrocalcinosis of the knee or wrist. Conclusion: CPPD crystal formation seems to be a late and frequent event of tophus maturation, occurring more frequently with aging, and could contribute to the speed of tophus dissolution and the apparent persistence of tophus sometimes observed even after effective, long‐lasting urate‐lowering therapy.